2017
DOI: 10.2135/cropsci2016.09.0821
|View full text |Cite
|
Sign up to set email alerts
|

Fine Mapping of qFIS1‐2, a Major QTL for Kernel Fissure Resistance in Rice

Abstract: W hen rice (Oryza sativa L.) is milled to remove the hull and bran layer, the resulting white rice is graded according to physical properties. A key component determining the grade or economic value for a consignment of rice is its milling quality, which is defined by the proportion (in mass) of rice that remains intact (unbroken) after milling. After rice is milled, the broken kernels (defined as having grain length less than three-fourths the sample average) are separated from the unbroken rice (also known T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…An association between taller height and increased kernel fissuring was detected in all four environments. This was unexpected because previous reports of association between PH and FR indicated that their correlations were due to physical linkage between qFIS1‐2 and the sd‐1 semidwarf gene, an association that the qFIS1‐2 fine mapping study (Sater et al, 2017) documented to be due to physical linkage that could be broken by recombination. As both Cybonnet and Saber are sd‐1 semidwarfs (McClung et al, 2004; Gibbons et al, 2006), the CS‐RILs do not segregate for this trait, but they apparently segregate for other PH genes, as evidenced by transgressive segregation among the CS‐RILs (Table 1).…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…An association between taller height and increased kernel fissuring was detected in all four environments. This was unexpected because previous reports of association between PH and FR indicated that their correlations were due to physical linkage between qFIS1‐2 and the sd‐1 semidwarf gene, an association that the qFIS1‐2 fine mapping study (Sater et al, 2017) documented to be due to physical linkage that could be broken by recombination. As both Cybonnet and Saber are sd‐1 semidwarfs (McClung et al, 2004; Gibbons et al, 2006), the CS‐RILs do not segregate for this trait, but they apparently segregate for other PH genes, as evidenced by transgressive segregation among the CS‐RILs (Table 1).…”
Section: Resultsmentioning
confidence: 86%
“…Although the QTL intervals were long and overlapping, the locations of their LOD peaks varied between the environments by as much as 20 cM (Table 2); variable LOD peak locations between environments was true for all FR QTLs except qFIS5 , which mapped consistently to 22 to 24 cM. The fact that the LOD peak for qFIS1‐2 using across‐environment LSMean data mapped precisely to the known, fine‐mapped location (Sater et al, 2017) indicates confidence in the all QTL estimates based on LSMean data as well, it but underscores the need for numerous replications for proper evaluation of FR.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations